Letters from a Young Shaker William S. Byrd at Pleasant Hill ; edited by Stephen J. Stein. - Byrd, William S., 1806-1829.; Stein, Stephen J., 1940- (Lexington : The University Press of Kentucky, 2015)
In the early nineteenth century, a young man belonging to the prominent Byrd family of Virginia, the grandson of William Byrd III, took up residence in the Shaker community at Pleasant Hill, Kentucky. Over the next two years, 1826--1828, he wrote a series of letters to his father, a federal judge in Ohio, describing his experiences and his impressions of the United Society of Believers, as the Shakers were formally called. Eventually, William S. Byrd became a convert to the society and an advocate of its beliefs and practices. His letters -- cut short by his father's death -- offer today's rea.
Cover; Title; Copyright; Contents; List of Illustrations; Preface; Introduction; The Letters of William S. Byrd to Charles Willing Byrd; Appendixes; Notes; Index; A; B; C; D; E; F; G; H; I; J; K; L; M; N; O; P; Q; R; S; T; U; V; W; Y
Description based upon print version of record.
Includes index.
Keywords: Byrd, William S., -- 1806-1829.; Shakers -- Kentucky -- Pleasant Hill -- Correspondence; Pleasant Hill (Ky.) -- History; RELIGION / Christianity / Denominations; Electronic books